A knowledge management and information portal for the Kazakhstan Atomic Energy Committee. (21st September 2009) - Kosilov, A.; Mandl, W.; Pasztory, Z.; Gladyshev, M.; Idrissova, M.; Zhantikin, T.
This paper has been prepared in close collaboration between the International Atomic Energy Agency (IAEA) Department of Technical Cooperation (TC), IAEA's International Nuclear Information System (INIS) and Nuclear Knowledge Management Section and representatives of the Kazakhstan Atomic Energy Committee (KAEC) of the Ministry of Energy and Mineral Resources of the Republic of Kazakhstan. The KAEC's knowledge management and information portal will provide a comprehensive, modern tool for integrated information and knowledge management. Implemented in several consecutive stages, it will – right from the beginning – have a positive impact on the working efficiency and reliability of the tasks performed at the KAEC by providing a set of key tools that will support the existing business model. In its final implementation stage, it will provide both the means and the incentive to replace current business procedures with a new, highly efficient, transparent and reliable approach.